ANALISIS PENGARUH LINGKUNGAN JASA (SERVICESCAPE) TERHADAP KEPUASAN KONSUMEN DENGAN NILAI PENGALAMAN DAN KONEKSI MEREK DIRI SEBAGAI VARIABEL INTERVENING (STUDI PADA PENGUNJUNG LAWANG SEWU SEMARANG) - Andhika, Sielvi; Ferdinand, Augusty Tae (Diponegoro Journal of Management, 2019)
Tourism has become a promising business sector in developments in various circumstances. Each step with a dynamic routine so that the development of tourism business follows the harmony of patterns and lifestyles. Holidays become a necessity for every individual when routines become more solid and dynamic. A useful opportunity for business people to develop the tourism sector. This opportunity makes the company must be able to survive and develop in determining the right strategies and business decisions. The purpose of this study was to determine the effect of the service environment, the value of experience, and self-brand connections to consumer satisfaction in Semarang Tourism Lawang Sewu.This study uses a non-probability sampling technique as a sampling technique and purposive sampling method with the criteria of respondents being visitors to Lawang Sewu. The responses of 145 respondents were analyzed using the Structural Equation Model (SEM) analysis tool, and the AMOS (Analysis of Moment Structure) estimation tool. The results of the study show that servicescape, experiential value, and self-brand connection have a significant and positive effect on customer satisfaction.